In the Whirlwind: God and Humanity in Conflict - Burt, Robert A. (Harvard Univ. Press, 2012)
God deserves obedience simply because he’s God—or does he? Inspired by a passion for biblical as well as constitutional scholarship, in this bold exploration Yale Law Professor Robert A. Burt conceptualizes the political theory of the Hebrew and Christian Bibles. God’s authority as expressed in these accounts is not a given. It is no less inherently problematic and in need of justification than the legitimacy of secular government. In recounting the rich narratives of key biblical figures—from Adam and Eve to Noah, Cain, Abraham, Moses, Job, and Jesus—In the Whirlwind paints a surprising picture of the ambivalent, mutually dependent relationship between God and his peoples. Taking the Hebrew and Christian Bibles as a unified whole, Burt traces God’s relationship with humanity as it evolves from complete harmony at the outset to continual struggle. In almost every case, God insists on unconditional obedience, while humanity withholds submission and holds God accountable for his promises.Contemporary political theory aims for perfect justice. The Bible, Burt shows, does not make this assumption. Justice in the biblical account is an imperfect process grounded in human—and divine—limitation. Burt suggests that we consider the lessons of this tension as we try to negotiate the power struggles within secular governments, and also the conflicts roiling our public and private lives.